P PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBANTUAN EDPUZZLE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA - Pantin, Liselsi Dwi Shine Putria; Junarti; Khoirotunnisa’, Anis Umi (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
Understanding mathematical concepts is crucial to students' success in solving mathematical problems. Improving this understanding requires a contextual learning model that supports active student engagement. This study examines the Contextual Teaching and Learning (CTL) model, which emphasizes the connection between lesson material and real life, and Edpuzzle, which supports interactive learning through videos with embedded questions. This study aims to examine the differences in the effects of the CTL model with Edpuzzle assistance and the conventional model on students' ability to understand mathematical concepts, as well as to test whether the CTL model with Edpuzzle assistance yields better results than the conventional model. The study employed a quasi-experimental method with a nonequivalent control group design. The subjects were 83 seventh-grade students at MTs Walisongo Sugihwaras, divided into an experimental class (CTL assisted by Edpuzzle) and a control class (conventional). There were five meetings, and pre- and post-tests were administered. Data collection techniques included tests, observations, and documentation. The data analysis revealed that the post-test scores of the experimental class students (average 79.6) were higher than those of the control class students (average 55). The t-test at a 5% significance level yielded a value of t-calculated= 12.017 > t-table= 2.021. Since the post-test data were non-homogeneous, the test was conducted under the assumption of unequal variances. These results suggest that the CTL model, when assisted by Edpuzzle, improves students' ability to comprehend mathematical concepts. Compared to the conventional model. These findings suggest that using a digital, technology-based, contextual approach is a promising strategy for learning.